Marketing digital y mejora de la relación con los usuarios: Unidad De Bienestar Estudiantil. - Chuchuca Ajila, Jessica Cecilia (My University, 2018)
Digital marketing is important to use to generate links between users and improve communication through digital media. The purpose of this research is to improve the relationship with users of the Student Welfare Unit of the Technical University of Machala with the aim of proposing a digital marketing program through market research, determining aspects such as defining the factors of digital marketing, establish the most appropriate digital marketing channels to reach the university community and identify the level of knowledge about the Student Welfare Unit services. The quantitative methodology was used with the simple random sampling which was done to students of the Technical University of Machala, identifying the population the convenience sampling was applied to 33 Marketing Engineering students through the survey to investigate the knowledge level of the students services and interaction between the students and the unit and the digital media which verified the scarce knowledge about the services and few means of digital communication to transmit information and interact with the users. With the research, it was possible to identify the factors and channels of digital marketing to reach user satisfaction and communicate through digital media with the student directly and improve the relationship.
El marketing digital es importante emplear para generar vínculos entre los usuarios y mejorar la comunicación a través de los medios digitales. La presente investigación tiene como propósito mejorar la relación con los usuarios de la Unidad de Bienestar Estudiantil de la Universidad Técnica de Machala con el objetivo de proponer un programa de marketing digital a través de una investigación de mercado, se determinó aspectos como definir los factores de marketing digital, establecer los canales de marketing digital más apropiados para llegar a la comunidad universitaria e identificar el nivel de conocimiento acerca de los servicios de Unidad de Bienestar Estudiantil. Se empleó la metodología cuantitativa con el muestreo aleatorio simple la cual se realizó a estudiantes de la Universidad Técnica de Machala, identificando la población se aplicó el muestreo por conveniencia a 33 estudiantes de Ingeniería en Marketing mediante la encuesta para investigar el nivel de conocimiento de los servicios e interacción entre los estudiantes y la unidad y los medios de comunicación digital la cual se verificó el escaso conocimiento acerca de los servicios y pocos medios de comunicación digital para transmitir información e interactuar con los usuarios. Con la investigación permitió identificar los factores y canales de marketing digital para llegar a la satisfacción del usuario y comunicar a través de medios digitales con el estudiante de forma directa y mejorar la relación.
Keywords: MARKETING DIGITAL; INSTITUCIÓN PÚBLICA; FACTORES DE MARKETING DIGITAL; CANALES DE MARKETING DIGITAL